Numerical study on failure process and ultimate state of steel bearing under combined load. Issue 4 (April 2020) - Gibe, Hagere Alemayehu; Tamai, Hiroki; Sonoda, Yoshimi
Abstract: The limit state and deformation performance of steel bearing under seismic load is one of the most critical points to consider the effective or rational design of bridge against strong ground motion. In the 2016 Kumamoto earthquake, various bridges are damaged by the earthquake. Among the components of the bridge, steel bearings are the most damaged part of the bridge, which affects the functionality of the entire bridge. Since the 1995 Southern Hyogo Prefecture Earthquake, several studies about the ultimate state of steel bearing during earthquake carried out. However, there are a few studies on analyzing the failure processes and ultimate state of steel bearing when various loads assumed at the time of the earthquake. Therefore, the study investigates the failure process and ultimate state of pin bearing and pin-roller bearing under combined load using static push-over analysis. First, the bridge axis and perpendicular bridge axis horizontal loading directions proposed depending on the actual earthquake directional behavior of the bridge. Then the analysis of each bearing conducted and clarified the failure process of each bearing that leads to failure based on the von mises stress yield criteria. Three-dimensional finite element method used to analyze the bearings. The analysis result found that set bolt and pin neck tensile failure were the probable failure mode of pin bearing, and failure mode of pin-roller bearing depends on vertical and horizontal loading direction. In the future, the result used to propose a new seismic resistance design and reinforcement method of bearings that satisfies the required performance. Abstract : Civil engineering; Structural engineering; Earthquake engineering; Structural analysis; Structural mechanics; Pin bearing; Pin-roller bearing; Failure process; Ultimate load capacity; Bridge axis; Perpendicular bridge axis; Dead load; Uplift load; FEM